Ambidexterity and IT competence can improve supply chain flexibility? A resource orchestration approach. Issue 2 (March 2020) - Rojo Gallego Burin, Araceli; Perez-Arostegui, Maria Nieves; Llorens-Montes, Javier
Abstract: Supply chain flexibility (SCF) has become an important competitive weapon for companies in the current dynamic environment. This paper explores the influence of ambidexterity on supply chain flexibility (SCF) and theorizes the moderating effect of information technology (IT) competence on that relationship. Whereas prior research focuses on the positive results of SCF for business performance, little empirical research has studied its facilitators, leaving the gap this study seeks to fill. We draw on resource orchestration theory to develop our research model. According to this theory, a firm can exploit the full potential of its resources and capabilities only when these are deployed in a complementary manner. This study proposes that ambidexterity impacts SCF positively and that its effect is amplified when the firm possesses IT competence. In order to test our hypotheses we have employed a hierarchical regression methodology and put into service data collected from manufacturing enterprises. The study confirms that ambidexterity, as the ability to explore and exploit SC resources, enables their orchestration, making SC resources flexible, and a high IT competence facilitates that orchestration. Highlights: Supply chain ambidexterity positively affects supply chain flexibility. The relationship between ambidexterity and supply chain flexibility is amplified when information technology competence is high. ROT is adequate for understanding the complementariety of ambidexterity and IT competence on developing SCF. The study proves that ambidexterity, enables the orchestration of SC resources, and IT competence facilitates that orchestration.